2022
DOI: 10.1186/s12868-022-00756-2
|View full text |Cite
|
Sign up to set email alerts
|

NLRP3 inflammasome regulates astrocyte transformation in brain injury induced by chronic intermittent hypoxia

Abstract: Background Obstructive sleep apnea (OSA) is mainly characterized by sleep fragmentation and chronic intermittent hypoxia (CIH), the latter one being associated with multiple organ injury. Recently, OSA-induced cognition dysfunction has received extensive attention from scholars. Astrocytes are essential in neurocognitive deficits via A1/A2 phenotypic changes. Nucleotide oligomerization domain (NOD)-like receptor protein 3 (NLRP3) inflammasome is considered the most important factor inducing and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…OSA alters exosomal carriers in circulation, especially miRNAs, and promotes endothelial dysfunction [68]. Several in vivo studies have demonstrated the involvement of miRNAs and the nucleotide-binding domain-like receptor protein 3 (NLRP3) inflammasome in chronic IH-induced inflammation and tissue injury [36, [69][70][71][72][73][74][75]. During IH exposures, miRNAs such as miR-155 [69], miR-210 [70], and miR-144 [71] are upregulated in renal tissue, endothelium, and serum-derived extracellular vesicles, respectively; the silencing of these miRNAs ameliorate IH-induced inflammation, endothelial dysfunction, and tissue injury [69][70][71].…”
Section: Mirna/nlrp3 Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…OSA alters exosomal carriers in circulation, especially miRNAs, and promotes endothelial dysfunction [68]. Several in vivo studies have demonstrated the involvement of miRNAs and the nucleotide-binding domain-like receptor protein 3 (NLRP3) inflammasome in chronic IH-induced inflammation and tissue injury [36, [69][70][71][72][73][74][75]. During IH exposures, miRNAs such as miR-155 [69], miR-210 [70], and miR-144 [71] are upregulated in renal tissue, endothelium, and serum-derived extracellular vesicles, respectively; the silencing of these miRNAs ameliorate IH-induced inflammation, endothelial dysfunction, and tissue injury [69][70][71].…”
Section: Mirna/nlrp3 Signalingmentioning
confidence: 99%
“…In animal models, chronic IH exposure increases NLRP3 inflammasome expression, and NLRP3 deficiency or inhibition protects against IH-induced inflammation, oxidative stress, and apoptosis in the brain, heart, and vasculature [36, [72][73][74][75]. Additionally, in vitro IH exposure fails to induce IL-1β overproduction in bone marrow-derived macrophages isolated from NLRP3 knockout male mice [87], reinforcing the involvement of NLRP3 in IH-induced inflammation.…”
Section: Mirna/nlrp3 Signalingmentioning
confidence: 99%
“…Conversely, the "neuroprotective" phenotype of astrocytes promotes neuronal survival and homeostasis, as these astrocytes secrete neurotrophic factors and anti-inflammatory cytokines [184,187,188]. Currently, published studies suggest that NLRP3 inflammasome activation and subsequent secretion of IL-18 and IL-1β from microglia drives astrocytes into the neurotoxic reactive state, which induces upregulation of the secretion of the complement protein C3 and results in lower synapse numbers [180,[189][190][191]. However, these studies evaluated astrocyte state upon NLRP3 inflammasome activation based on the binary "A1/A2" astrocyte description, which does not fully capture the diversity of astrocyte states and phenotypes in different contexts [183].…”
Section: Consequences Of Microglial Nlrp3 Inflammasome Activation On ...mentioning
confidence: 99%
“…Then, it leads to the release of caspase-1 and IL-1β ( He et al, 2016 ). A recent study indicated that the NLRP3 inflammasome expression was increased in the brain tissue after IH treatment ( She et al, 2022 ). Meanwhile, NLRP3 deletion elicited neuroprotection against IH treatment eliminating damaged mitochondria and reducing oxidative stress levels ( Wu et al, 2021 ).…”
Section: Pathophysiology Of Cognitive Impairment In Osamentioning
confidence: 99%